2000
DOI: 10.1074/jbc.275.4.2479
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin Differentially Regulates the Chemokine Receptor CXCR4-mediated Signaling and Receptor Internalization, and This Implicates Multiple Interaction Sites between β-Arrestin and CXCR4

Abstract: The chemokine receptor CXCR4 has recently been shown to be a co-receptor involved in the entry of human immunodeficiency virus type 1 into target cells. This study shows that coexpression of ␤-arrestin with CXCR4 in human embryonic kidney 293 cells attenuated chemokine-stimulated G protein activation and inhibition of cAMP production. Truncation of the C-terminal 34 amino acids of CXCR4 (CXCR4-T) abolished the effects of ␤-arrestin on CXCR4/G protein signaling, indicating the functional interaction of the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
202
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(229 citation statements)
references
References 45 publications
23
202
0
4
Order By: Relevance
“…␤-Arrestins quench some signals from the activated receptor such as in cAMP-dependent protein kinase pathways, and they mediate other signals such as those involved in the MAPK cascades. It has been reported that ␤-arrestins play a crucial role in ␤ 2 -adrenergic receptormediated ERK activation (39), and our previous work also demonstrates that ␤-arrestin2 can enhance the CXCR4-mediated activation of ERK (21). Our current study further reveals that ␤-arrestin2 is crucially involved in the chemokine-induced activation of p38 MAPK.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…␤-Arrestins quench some signals from the activated receptor such as in cAMP-dependent protein kinase pathways, and they mediate other signals such as those involved in the MAPK cascades. It has been reported that ␤-arrestins play a crucial role in ␤ 2 -adrenergic receptormediated ERK activation (39), and our previous work also demonstrates that ␤-arrestin2 can enhance the CXCR4-mediated activation of ERK (21). Our current study further reveals that ␤-arrestin2 is crucially involved in the chemokine-induced activation of p38 MAPK.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous study demonstrates that ␤-arrestin can functionally interact with CXCR4 on SDF-1 stimulation and thus significantly attenuate CXCR4-mediated G-protein activation and promote CXCR4 internalization (21). Recent discoveries indicate that ␤-arrestin also plays an important role as a scaffold that links GPCRs to mitogen-activated protein kinase (MAPK) cascades such as Raf, ERK, ASK1, and c-Jun NH 2 -terminal kinase 3 (22).…”
mentioning
confidence: 99%
“…This suggests that receptor phosphorylation is not a critical determinant of ␤-arrestin recruitment to the agonist-occupied CCR5. Alternatively, serine residues in the ICLs may be phosphorylated by GRKs and serve as ␤-arrestin recruitment sites, as has been shown previously for CXCR4 (Cheng et al, 2000). Fourth, substituting the C-tail of CCR5 for the C-tail of CXCR4 transferred the slow trafficking phenotype of CCR5 to the X4-R5 chimera.…”
Section: Discussionmentioning
confidence: 73%
“…For some receptors, the intracellular loops are important for interaction with arrestins (51-54); for some, it is the C terminus (55)(56)(57)(58)(59)(60), and for others, both the loops and the C terminus may interact with arrestins but with different affinities (61). Our previous results demonstrated that truncation of the C terminus of the human PAFR from cysteine 317 abrogated receptor internalization (39).…”
Section: Discussionmentioning
confidence: 99%